Online nutritional counseling and assessment: A potential tool for the present and the near future - Pérez-Beltrán, Yolanda E.; González- Becerra, Karina; Rivera-Iñiguez, Ingrid; Sáyago-Ayerdi, Sonia G.; Mendivil, Edgar J. (Revista Española de Comunicación en Salud, 2023)
Introduction: Care and attention to people’s health is an objective of professionals in this area. Comprehensive strategies are being sought to reduce the alarming prevalence of obesity in populations around the world, coupled with the restructuring of the health system that came as a consequence of the COVID-19 pandemic, different tools, such as online nutrition counseling, have been incorporated to embrace the needs and provide a service in favor of the population. Objective: To evaluate the effect of online nutrition counseling on anthropometric parameters of overweight and obese adults. Methodology: Thirty individuals were enrolled in an online nutritional intervention and followed a weight control diet for 8 weeks. Every 15 days, the participants received nutritional counseling through virtual platforms. Anthropometric parameters were evaluated at the beginning, middle and end of the intervention, the physical activity performed by the participants was calculated, and an emotional eating questionnaire was applied. Results: Significant changes were observed in baseline versus final anthropometric parameters. 30% of participants reported an increase in the physical activity performed, and 31% indicated improvements in the influence of emotions on their eating habits. Conclusion: Online nutrition counseling is a feasible and reliable strategy to provide and receive nutritional care remotely.
Keywords: online couseling; nutrition; multimedia; overweight; obesity